Effects of structured exercise regime on lipid profile and renal function tests in gestational diabetes mellitus patients-A pilot study - Wardah Ajaz Qazi; Muhammad Naveed Babur; Arshad Nawaz Malik; Nadia Ahmed Bokhari; Mirza Shamim Baig; Ruqia Begum (Journal of the Pakistan Medical Association, 2020)
<p style="box-sizing: border-box; margin: 0px; line-height: 1.6; color: #000000; font-family: 'Open Sans', sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Notes of Concern: Article published in Journal of Pakistan Medical Association J Pak Med Assoc.February 2021, No. 2-A,Volume 72 Pages 505-507. <p style="box-sizing: border-box; margin: 0px; line-height: 1.6; color: #000000; font-family: 'Open Sans', sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">This editorial expression of concern serves to notify readers that the Editorial Board has identified discernible weaknesses in the study design, statistical concerns and conclusion drawn regarding this previously published article, titled: "Effects of structured exercise regime on lipid profile and renal function tests in gestational diabetes mellitus patients-A pilot study" J Pak Med Assoc. Vol. 71, No. 2-A, February 2021 pages 505-507. <p style="box-sizing: border-box; margin: 0px; line-height: 1.6; color: #000000; font-family: 'Open Sans', sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">The Editorial Board has determined that : <ul style="box-sizing: border-box; margin: 12px 0px 12px 50px; padding: 0px; color: #000000; font-family: 'Open Sans', sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; list-style-type: none;"> 1. The article did not discuss the feasibility of the pilot study, instead attempted to draw inference from the analytical outcomes, which does not allow readers to interpret the desired implications correctly. 2. The statistical methods applied were not at par and did not use the baseline data. The authors did not make full use of the data to add to the scientific weightage of the study, which could have been reported in the text. 3. The conclusion only points towards the positive impacts on serum markers for diabetes mellitus and renal functions. Considering the very small sample size used, this is an unjustified extrapolation. The authors did not attempt to mention the feasibility of the whole process, including participants' willingness, management, and resources that should have been assessed and reported to benefit the planning of the full-scale RCT. <p style="box-sizing: border-box; margin: 0px; line-height: 1.6; color: #000000; font-family: 'Open Sans', sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">The editorial board of JPMA decided to publish this editorial expression of concern when we were made aware of deficiencies in the published article so that future researchers can plan their work on better scientific footings. -------------------------------------------------------------------------------------------------------------------- Objectives: To determine the effects of structured exercise regime on biochemical markers of patients of gestational diabetes mellitus during the third trimester. Methods: The two-arm pilot study was conducted at the Fauji Foundation Hospital, Rawalpindi, Pakistan, from March to July 2019, and comprised women aged 20-40 years with gestational age >20 weeks who were diagnosed with gestational diabetes mellitus and who were able to do 6min walk test under severity level on the 0-10 Borg scale. The subjects were randomized into two groups using the sealed envelope method. The intervention group received 5 weeks of structured exercise programme. including aerobics, stabilisation and pelvic floor muscle training, while the control group only received postural education. Data was noted at baseline and after intervention, and was analysed using SPSS 20. Results: Of the 16 subjects, there were 8(50%) in each of the two groups. The mean age was 31.5±4.17 years in the interventional group and it was 35.0±6.30 years in the control group. Serum low-density lipoprotein and serum creatinine showed significant differences between the groups (p<0.05), while the rest of markers were non-significant (p>0.05). Conclusion: Structured exercise regime was found to have a positive effect in reducing serum low-density lipoprotein and serum creatinine levels in gestational diabetes mellitus during the third trimester. Key Words: Gestational diabetes mellitus, Lipid profile, Renal function tests, Structured exercise regime, Third trimester.